EVALUATION AND SELECTION OF SEED NUMBER IN THE FRUIT OF CAPPARIS SPINOSA L BASED ON PRODUCTIVITY INDICATORS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Of particular importance is the scientific basis for the germination of seeds of the plant Capparis spinosa L.